Stabilization of peat soil using electrochemical injection technique - Moayedi, Hossein (2012)
The peat soils are naturally very soft and undergo large settlements. Due to its low shear strength and high compressibility, such soils are geotechnically problematic. To improve the physicochemical characteristics of the peat soil, electrokinetic (EK) injection technique was used by applying a direct electrical potential across the soil specimens. Four chemical reagents namely, sodium silicate (Na2SiO3), calcium oxide (CaO), calcium chloride (CaCl2), and aluminium hydroxide (Al(OH)3) were used as chemical stabilizers. A series of unconfined compressive strength (UCS), pH, water content, microstructure analysis, surface electrical charge, and rheology on the treated soil were conducted. The UCS values for stabilized peat soil samples were optimized at the 8, 6, 6, and 4%, of sodium silicate, calcium oxide, calcium chloride,and aluminum hydroxide respectively. However, the UCS values were decreased beyond the mentioned percentages for all the samples. The surface electrical charge properties of the peat treated with chemical stabilizers in different molarities and pH were also investigated. The average natural pH of peat soil samples was found to be equal to 5.93 with  potential of 17.05 mV. The chemical stabilizer type and concentration showed an important effect on the surface electrical charge of peat soil particles. Lastly, a large scale EK equipment was developed to inject chemical stabilizer through the baseline peat soil in order to enhance its undrained shear strength, pH, and moisture content characteristics. The undrained shear strength (measured by van shear test), soil pH, and moisture content of treated soil with the large EK instrument were measured. It was found that the undrained shear strength of treated soils was increased by interparticle cementation caused by the electrochemical injection of ions into the soil under the DC field. It can be concluded that injecting chemical stabilizer by using the EK technique could significantly increase the treated soil shear strength and decrease its moisture content.